Blood Lead Exposure and Association With Hepatitis B Core Antibody in the United States: NHANES 2011–2018 - Han, Kexing; He, Tengyao; Huang, Siran; Sun, Weijie; Gao, Yufeng (Frontiers in Public Health, 2022)
The objective of this project was to explore the distribution and related factors of serum lead and the association between serum lead and hepatitis B core antibody (HBcAb). All the data were from the US National Health and Nutrition Examination Survey (NHANES). 15,097 (aged 20 to 80 years) participants were included totally. Participants without a history of blood transfusion were more likely to be exposed to lower levels of serum lead [-2.30(-3.13, -1.47) for HBcAb(-) and -2.23(-4.54, 0.08) for HBcAb(+)]. The odds ratio of HBcAb(+) increased with serum lead and got the result was 1.09(95%CI:1.06,1.12). This study showed that older, male, lower education level, lower PIR, lower BMI, history of blood transfusion, lived with companion, Total number people in the family>3, longer time of US residence, citizen by birth or naturalization, and non-US birth was associated with higher serum lead exposure and Serum lead had a positive association with HBcAb(+).